2001
DOI: 10.1074/jbc.m009449200
|View full text |Cite
|
Sign up to set email alerts
|

A STAT-responsive Element in the Promoter of the Episialin/MUC1 Gene Is Involved in Its Overexpression in Carcinoma Cells

Abstract: The mucin-like glycoprotein episialin (MUC1) is highly overproduced by a number of human carcinomas. We have shown previously in a variety of mammalian cell lines that overexpression of this very large transmembrane molecule diminishes cellular adhesion, suggesting that episialin/MUC1 overexpression may play an important role in tumor invasion and metastasis. By using in situ hybridization, we show here that episialin/ MUC1 mRNA expression can be increased more than 10-fold in breast carcinoma cells relative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
119
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(127 citation statements)
references
References 55 publications
6
119
0
2
Order By: Relevance
“…As found for normal breast epithelia, breast cancer, and uterine cell lines, 18,26,39 we observed strong cytokine influences on MUC1 expression in normal prostate epithelia and certain prostate cancer cell lines (PC-3). In other prostate cancer cell lines, MUC1 either was constitutively expressed at high levels (DU-145) or not detected under any condition (LnCaP and derivative cell lines).…”
Section: Pc-3 Cells Differ From That Of Mitchell Et Alsupporting
confidence: 81%
See 1 more Smart Citation
“…As found for normal breast epithelia, breast cancer, and uterine cell lines, 18,26,39 we observed strong cytokine influences on MUC1 expression in normal prostate epithelia and certain prostate cancer cell lines (PC-3). In other prostate cancer cell lines, MUC1 either was constitutively expressed at high levels (DU-145) or not detected under any condition (LnCaP and derivative cell lines).…”
Section: Pc-3 Cells Differ From That Of Mitchell Et Alsupporting
confidence: 81%
“…In light of studies indicating that MUC1 expression is stimulated by steroid hormones and cytokines in other systems, 18,25,26 we evaluated the ability of IFN-g, TNF-a, and DHT to induce MUC1 expression in PrEC and prostate cancer cell lines. PrEC expressed moderately higher amounts of MUC1 after treatment with IFN-g or TNF-a alone; however, combined cytokine treatment produced a highly synergistic increase in MUC1 expression.…”
Section: Resultsmentioning
confidence: 99%
“…The MUC1 oncoprotein is aberrantly overexpressed in about 90% of human breast tumors (1,17). MUC1 overexpression is conferred, at least in part, by up-regulation of MUC1 mRNA levels at the transcriptional level (18)(19)(20)(21). MUC1 interacts with ER and certain other transcription factors, and thereby contributes to the regulation of gene expression (7,22).…”
Section: Discussionmentioning
confidence: 99%
“…16 In addition, production of the antiinflammatory IL-10 and type I interferon (IFN) has been shown to correlate with increased MUC1 expression. [17][18][19] Investigations in mice with Helicobacter pylori-induced gastritis revealed that Muc1 expression negatively regulates the NLRP3 inflammasome, which mediates production of IL-1b. 20 Taken together, these data suggest that in addition to a barrier role to infection, MUC1 may also be involved with regulation of inflammation in response to infection.…”
Section: Introductionmentioning
confidence: 99%